2020
DOI: 10.1101/2020.08.16.252940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Vitamin-D receptor (VDR) by a small molecule antagonist MeTC7 inhibits PD-L1 but controls THMYCN neuroblastoma growth PD-L1 independently

Abstract: Vitamin-D receptor (VDR) mRNA is enriched in malignant lung, ovarian and pancreatic tissues and showed poor prognoses. Calcitriol and stable or CRISPR-directed VDR upregulation increased PD-L1mRNA and protein expression in cancer cells in-vitro. A ChIP assay showed the binding of VDR with VDREPD-L1. Stattic, a STAT3 phosphorylation inhibitor blocked calcitriol or VDR overexpression induced PD-L1 upregulation. MeTC7, a VDR antagonist developed by us, reduced PD-L1 expression on macrophages, ovarian, lung, breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Antagonist of VDR reduced PD-L1 expression on many cancer cells lines including lung. Also, suppressed inflammatory monocytes and increased intra-tumoral CD69 + PD1 + CD8 + T cells [18]. This may explain the role of vitamin D in cancer by binding with VDR so, may prevent binding of VDR with PDL-1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Antagonist of VDR reduced PD-L1 expression on many cancer cells lines including lung. Also, suppressed inflammatory monocytes and increased intra-tumoral CD69 + PD1 + CD8 + T cells [18]. This may explain the role of vitamin D in cancer by binding with VDR so, may prevent binding of VDR with PDL-1.…”
Section: Discussionmentioning
confidence: 94%
“…Low levels of vitamin D is recognized as a consequence of chronic inflammation rather than the cause [33]. Calcitriol treatment transcriptionally upregulated PDL-1 gene and protein expression in cancer cells, and that VDR is overexpressed in malignant tissues of pancreatic, ovarian, and lung cancer compared to normal controls and was correlated with poor prognosis [18]. Yu et al ensured that PDL-1 expression has emerged as a biomarker that predicts which patients are more likely to respond to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, vitamin D is being extensively examined as a promising tool in cancer immunotherapy when administered concomitantly with checkpoint inhibitors, 15 as the induced PD‐L1 due to vitamin D positively correlate with the response to immune checkpoint inhibitors 16 . It was also shown that dual blockade of C‐X‐C motif ligand 12 (CXCL12) and PD‐1‐PD‐L1 synergistically increases an effective immune response.…”
Section: Introductionmentioning
confidence: 99%